(untitled) (Bangladesh Journal of Zoology, 2025)
As the risks associated with vector-borne diseases continue to rise due to climate change and human activities, understanding the current diversity of mosquito species across different habitats is crucial. The current study aimed to assess the diversity, distribution, richness and relative abundance of mosquito species (Diptera: Culicidae) in Dhaka, Bangladesh. A total of 2,147 mosquito specimens were collected between September to November 2023 from six distinct locations of Dhaka district, employing the BG-1 sentinel traps. Ten mosquito species were identified: Aedes aegypti, Aedes albopictus, Culex quinquefasciatus, Culex tritaeniorhynchus, Culex fuscochephala, Culex bitaeniorhynchus, Mansonia annulifera, Mansonia indiana, Mansonia uniformis and Armigeres subalbatus. Culex tritaeniorhynchus was the most abundant species (63.68%), found in all surveyed areas followed by Culex quinquefasciatus (18.57%) and Aedes aegypti (13.02%). Notably, the highest number of Aedes aegypti (6.85%) was trapped in Dhaka north city corporation followed by Dhaka south city corporation (5.31%) and savar (1.01%). Dhaka North city corporation had the highest diversity, with a Shannon-Wiener Index of 1.07 and a Simpson Index of 0.62. In contrast, Savar Upazila had the highest species richness (10 species). This study provides a snapshot of mosquito fauna over a three-month period, highlighting variations in species diversity, relative abundance and distribution across peri-urban and urban landscapes of Dhaka District. Bangladesh J. Zool. 53(2): 171-184, 2025